Hydro-Morphometric Analysis using Geospatial Technology: A Case Study of Wadi Gabgaba and Wadi Allaqi Watersheds, Southern Egypt-Northern Sudan - Hamdan, Ali M (Journal of Asian Scientific Research, 2020)
Hydro-morphometric parameters analysed to understand the hydrological process and are prerequisite for assessment of hydrological characteristics of surface water basin. The aim of this study is an attempt to determine the watershed characteristics and hydro-morphometric analysis using ASTER data and GIS techniques of the two largest basins and most extensive drainage systems (Wadi Gabgaba and Wadi Allaqi basins) in the eastern desert at Southern Egypt/Northern Sudan region. Thermal Emission and Reflection Radiometer (ASTER) data were used for preparing Digital Elevation Model (DEM), flow direction, stream orders, and slope maps. Geographical information system (GIS) was used in evaluation of drainage network characteristics, drainage texture, basin geometry, and relief aspects of morphometric parameters. Watershed boundary, flow direction, flow accumulation, stream ordering, and flow length have been prepared using Arc-Hydro Tool. Relief-aspect, contour, and slope have been prepared using Surface Tool in ArcGIS-10.5 software, and ASTER (DEM). More than 41 morphometric parameters of all aspects for study basins have been computed. The degrees of hazard due to flooding were analysed based on nine morphometric parameters which have an effect on the hydrologic behavior of the study basins. Correlation coefficient analysis is evaluated between morphometric variables with the help of statistical analysis for ascertaining the basins characteristics which helps in mapping hydrological potentiality and preparing a comprehensive plan for sustainable management of the watersheds.